The Effect of Conflict Management With Work Stress of Nurses in The Tgk Chik Ditiro Sigli Regional Hospital - Abqariah; Masri; Mukhlis; Nurul Atikah (CV. Inara, 2026)
Conflict is a problem that often arises in the nursing work environment. Good conflict management for nurses is essential so that the conflict that occurs has a functional impact so that it can reduce nurses' work stress. The purpose of this study was to identify the relationship between conflict management with work stress of nurses in the Tgk Chik Ditiro Sigli Regional Hospital. This type of research is quantitative; correlative with a cross-sectional study design. The study population was all nurses in the Tgk Chik Ditiro Sigli Regional Hospital. The sampling technique used total sampling with a total of 58 respondents. The data collection tool was a questionnaire. Data analysis used the Chi Square statistical test . The results of data processing showed that of the 30 nurses with good conflict management, most of the nurses' work stress levels were mild, namely 22 nurses (73.3%). Meanwhile, of the 28 nurses with poor conflict management, 17 nurses (40.5%) felt mild stress with their work. The results of the study generally found that there was an influence of conflict management on work stress (p-value = 0.000). Therefore, it can be concluded that conflict management has a significant impact on nurses' work stress . Hospital management is expected to facilitate nurses' education and training on conflict and conflict management, thereby improving their ability to select appropriate conflict management strategies.